Middle East and North Africa Economic Developments and Prospects, October 2012 : Looking Ahead After a Year in Transition - World Bank (Washington, DC, 2012)
The Arab Republic of Egypt, Tunisia, Libya and the Republic of Yemen are recovering after a period of economic growth decelerations accompanying the Arab Spring uprisings of 2011. Economic recovery was relatively quick, with industrial production recovering in a matter of months and, in the cases of Egypt and Tunisia, the growth dips of 2011 were smaller than the average growth declines observed around the year of transition during past transitions to democracy. Importantly, the growth decelerations and recovery have taken place in a weak global environment, with events in the Euro zone posing particular challenges to Tunisia, and to a lesser extent, Egypt. The report focuses on the economic developments and short-term outlook for four Middle East and North Africa (MENA) Economies, Tunisia, Egypt, the Republic of Yemen and Libya. These four countries are given special attention because each of them experienced a revolution and a major political change in 2011 and is undergoing a process of political transition toward democracy. The sudden change had important economic consequences. While other countries in the Middle East and North Africa are undergoing political change, the economic ramifications were muted as compared with the changes observed in the four MENA post-revolutionary economies.